Kontribusi Ikatan Mahasiswa Muhammadiyah (IMM) Komisariat Pondok Hajjah Nuriyah Shabran Terhadap Masyarakat Makamhaji dalam Bidang Pendidikan Islam Tahun 2015 - Musa, Maful (2016)
Muhammadiyah Students Association (IMM) Commissariat cottage Hajjah Nuriyah Shabran as part of the youth of Islam need to take a greater role in participatory cultural movement, to educate the community. Islamic education community is a process of understanding the teachings of Islam to the community so that people know how to be islamic correctly. The research focus is on Contributions of Muhammadiyah Students Association (IMM) Commissariat cottage Hajjah Nuriyah Makamhaji Shabran on society in the perspective of Islamic education. The principal issues in this study is the first, whatever the form of contributions of Muhammadiyah Students Association (IMM) Commissariat cottage Hajjah Nuriyah Shabran to society Makamhaji 2015. Both supporters and pursuer what factors in the various activities of Islamic education to the community of Makamhaji. This research is a field research and data sources used are through interview, observation and documentation as well as books that are relevant to this study to reinforce the notion in completing the study. Technical analysis of the data used in this research is qualitative descriptive analysis The conclusions of this research are: (1) The types of contributions of Muhammadiyah Students Association (IMM) Commissariat cottage Hajjah Nuriyah Makamhaji Shabran to society and consists of Wildlife education Qur'an recitation mothers, Islamic studies, preachers state Ramadan, speach of islamic, and sermons. (2) The center for Islamic education in the mosque community. (3) The method used is the Islamic education discussions, lectures, and frequently asked questions, (4) Supporting the smooth operation is the availability of adequate infrastructure, public enthusiasm and a good speaker. Whereas the inhibiting is religious pupils are less concerned about the community, looking for presenters and congregation less response.